Antibacterial Activity Of Methanol Extract Of Meranti Sarang Punai Cortex (Shorea parvifolia Dyer) Against Staphylococcus aureus And Propionibacterium acnes - Syafriana, Vilya; Rachmatiah, Tiah; Utama, Nitya Wita (Jurnal Farmasi Udayana; Spesial Issue, Desember 2020, 2020)
Shorea parvifolia Dyer (meranti sarang punai) is one of a woody plant in Indonesia which distributed across Sumatra and Kalimantan. Cortex of meranti sarang punai is known contains the secondary metabolite such as saponin, flavonoid, and tannin which can act as an antibacterial agent. The research was aims to know the antibacterial activity of methanol extract of meranti sarang punai against Staphylococcus aureus and Propionibacterium bacteria. Maceration was chosen as the extraction methods with methanol as a solvent. The antibacterial test was done by disc diffusion method in Nutrient Agar (NA) media with concentrations 5 %, 10%, 15%, 20%, 25%, and 30%; while the Minimum Inhibitory Concentration (MIC) was done by solid dilution method with concentrations 5 %, 4%, 3%, 2%, and 1% . The results showed that the methanol extract of meranti sarang punai has antibacterial activity against the S. aureus with Inhibitory Zone (IZ) at concentrations of 5%, 10%, 15%, 20%, 25%, and 30% respectively 16,68; 17,27; 18,41; 19,4; 20,57; and 21,46 mm, while against P. acnes was 12,61 ; 13,65 ; 14,57 ; 15,53 ; 16,58 ; and 17,46 mm. The MIC of methanol extracts of meranti sarang punai against the two bacteria was at concentration 2%.